Synthesis and Characterization of New 7-Chloroisatin Derivatives and Study of Their Potential Antioxidant Activity - Al-Khuzaie, Mohammed G.A.; Al-Kurdy, Masar J.; Al-Majidi, Suaad M.H. (Iraqi Journal of Science, 2025)
A series of novel spiro azetidine and thioazetidine scaffolds incorporating an isatin subunit were successfully synthesized. The protocol involved reacting Schiff base derivatives of 7-chloroisatin with phenyl isocyanate or phenyl thioisocyanate. The new derivatives were obtained in excellent yield and characterized by different techniques such as FTIR, HNMR and 13CNMR. Furthermore, in silico, in vitro, and in vivo investigations were performed to assess the bioactivity of prepared compounds as antioxidants. The in-silico analysis encompassed the evaluation of pharmacokinetic and pharmacodynamic properties for all compounds, revealing favorable characteristics. Subsequently, molecular docking studies were performed with two proteins: VEGFR-2 and ALR2. The results demonstrated good docking scores for compounds 1-4. The in vitro assessments involved the evaluation of the potential antioxidant activity of all compounds using two methods: the total antioxidant capacity method and the DPPH scavenging activity method. The results demonstrated that all compounds exhibited noteworthy to excellent antioxidant activity. Based on these findings, compound 2 was selected for further investigation in the in vivo study using rats. In the in vivo experiment, male rats were administered a dose of 200 mg/0.5ml DMSO/rat/ day of compound 2 for 4-weeks, and the concentrations of total antioxidant capacity and MDA in their serum were measured. The results indicated that compound 2 exhibited commendable performance as an antioxidant agent.